If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 5)(x + 8) = 0 Reorder the terms: (5 + 3x)(x + 8) = 0 Reorder the terms: (5 + 3x)(8 + x) = 0 Multiply (5 + 3x) * (8 + x) (5(8 + x) + 3x * (8 + x)) = 0 ((8 * 5 + x * 5) + 3x * (8 + x)) = 0 ((40 + 5x) + 3x * (8 + x)) = 0 (40 + 5x + (8 * 3x + x * 3x)) = 0 (40 + 5x + (24x + 3x2)) = 0 Combine like terms: 5x + 24x = 29x (40 + 29x + 3x2) = 0 Solving 40 + 29x + 3x2 = 0 Solving for variable 'x'. Factor a trinomial. (8 + x)(5 + 3x) = 0Subproblem 1
Set the factor '(8 + x)' equal to zero and attempt to solve: Simplifying 8 + x = 0 Solving 8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + x = 0 + -8 x = 0 + -8 Combine like terms: 0 + -8 = -8 x = -8 Simplifying x = -8Subproblem 2
Set the factor '(5 + 3x)' equal to zero and attempt to solve: Simplifying 5 + 3x = 0 Solving 5 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 0 + -5 3x = 0 + -5 Combine like terms: 0 + -5 = -5 3x = -5 Divide each side by '3'. x = -1.666666667 Simplifying x = -1.666666667Solution
x = {-8, -1.666666667}
| -22=5x-x+10 | | 480=48x-.6t^2 | | -33=5(x+3)+7x | | 3x-2y+c=0 | | -11=-1-2b | | C^2=160 | | 5(x+3)+9=3(x-4)+6 | | -4y-y=-15 | | n-1.5=5.1 | | 12/18=8/y | | 6-(-1+8i)-(-7-i)= | | (10x-5y)=1 | | 2-6(r-6)=2+6(r-2) | | 4a-7=-59 | | 85+5x+10=180 | | 14=3v+5(v-2) | | 4a-7=59 | | b=1.5mv | | 9-8q+4q= | | 2q+1q= | | 75=6x+5x+9 | | 52+2x-6=180 | | -5-2n=21 | | 3(5n)+14+6n=21 | | -2(3x+6)=12 | | x(x+5)=210 | | 2X^2+-8X=0 | | 5(r-2)=-16+6r | | (-2x+4)-(-6x-7)= | | 3x-45=2y | | -6(2x-1)=0 | | x^2-15=-7x+2 |